Observed sediment and solute transport from the Kangerlussuaq sector of the Greenland Ice Sheet (2006–2016). Issue 1 (1st January 2018) - Hasholt, Bent; van As, Dirk; Mikkelsen, Andreas B.; Mernild, Sebastian H.; Yde, Jacob C.
ABSTRACT: New measurements of Watson River sediment and solute concentrations and an extended river discharge record improved by acoustic Doppler current profiler (ADCP) measurements are used to calculate the total sediment and solute transport from a large ice-sheet sector in southern west Greenland. For the 2006–2016 period, the mean annual sediment and solute transport was 17.5 ± 7.2 × 10 6 t and 85 ± 30 × 10 3 t, respectively (standard deviation given). The highest annual transport occurred in 2010, attaining values of 29.6 × 10 6 t and 138 × 10 3 t, respectively. The corresponding annual average values of specific transport are 1.39 × 10 3 t km −2 a −1 for sediment and 6.7 t km −2 a −1 for solutes from the approximately 12, 600 km 2 (95% ice covered) catchment, yielding an area-average erosion rate of 0.5 mm a −1 . The specific transport is likely several times higher under the ice sheet near the margin where all meltwater passes than it is in the interior where the ice sheet is frozen to the bed. We conclude that the Greenland Ice Sheet is a large supplier of sediment and solutes to the surrounding fjords and seas. We find that the proglacial area can be a net source of sediments during high floods and we confirm that an increased amount of meltwater-transported sediments can explain the expansion of deltas around Greenland, contradictory to delta erosion observed elsewhere in the Arctic in recent years.